2017
DOI: 10.1097/iae.0000000000001193
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Multisystemic Autoimmune Diseases Without Ophthalmologic Manifestations

Abstract: The choroid may be subclinically involved in autoimmune diseases. However, the choroidal response seems to differ depending on the autoimmune disease. Infiltrative mechanisms specific for lupus may justify the thickened choroid found in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 35 publications
0
40
1
Order By: Relevance
“…The relation between the duration or cumulative dosage of HCQ and CT has provided inconsistent results in previous publications. 14,35 In our study, we did not observe a significant association between HCQ treatment duration or cumulative dosage and CT.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The relation between the duration or cumulative dosage of HCQ and CT has provided inconsistent results in previous publications. 14,35 In our study, we did not observe a significant association between HCQ treatment duration or cumulative dosage and CT.…”
Section: Discussioncontrasting
confidence: 73%
“…9 In recent years, this technique enabled us to characterize the morphology and thickness of the choroid in several ocular and systemic pathologies. [10][11][12] However, only a very limited number of publications have evaluated the choroid in SLE patients using EDI SD-OCT. [13][14][15][16] These studies had heterogeneous samples and presented contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…Thickening of the choroid, possibly caused by an infiltration of the choroid by inflammatory cells, has been demonstrated in the active phases of Vogt–Koyanagi–Harada disease (VKH), Behçet's disease, sympathetic ophthalmia, and posterior scleritis [2125]. Moreover, choroidal thickness seems to be subclinically involved in some systemic inflammatory diseases without ophthalmologic manifestations [26].…”
Section: Introductionmentioning
confidence: 99%
“…According to Altinkaynak et al SLE patients had thinner choroids than age and gender-matched controls [85]. On the other hand, Ferreira et al reported thicker choroids in these patients [86]. This difference may be due to the systemic disease activity state as in the first study all patients were "inactive" whereas in the latter study the disease activity state was not accessed.…”
Section: Spectral Domain Optical Coherence Tomographymentioning
confidence: 95%